A discrete-time fast terminal sliding mode for depth control of autonomous underwater vehicle - Sarif, Nira Mawangi (2021)
The Autonomous Underwater Vehicle (AUV) demonstrates highly nonlinear and complexity in dynamic model coupled with unstructured ocean environment. With limitation of actuator constraints, the only solution for AUV to overcome this challenge is by manipulating the control algorithms. Naturally, Discrete-Time Sliding Mode Control (DSMC) is an appropriate controller for nonlinear systems due to its insensitivity to perturbations. However, the implementation of DSMC on AUV system contribute to chattering effect, which leads to low control accuracy and decreased lifetime of the actuator. For this reason, the reaching law scheme is employed to DSMC law. As a result, the reaching time of state trajectory to sliding surface is prolonged, hence, the robustness of the controller against perturbations is debilitated. Therefore, the Discrete-Time Fast Terminal Sliding Mode Control (DFTSMC) with reaching law schemes is proposed to overcome this issue. DFTSMC is a hybrid form of Discrete-Time Terminal Sliding Mode Control (DTSMC) and DSMC. The combination of nonlinear component from DTSMC and liner component by DSMC guarantee fast and finite error state convergence. While the chattering effect significantly reduced by nonlinear component from DTSMC. A comprehensive simulation showed that DFTSMC is capable of shortening the error state convergence of 65%, the reaching time by 32%, and reducing the chattering effect by 68%, in comparison with DSMC. In other words, DFTSMC offers fast and finite transient response, alleviates chattering effect, and guarantees strong robustness against perturbations in comparison with DTSMC and DSMC. Furthermore, DFTSMC also provides better system response when compared with discrete Proportional Integral Derivative (PID) and Model Predictive Controller (MPC). This indicates that DFTSMC is capable of providing better performance, compared with DTSMC, DSMC, discrete PID and MPC. Therefore, DFTSMC may emerge as one of the preferable controller methods towards improving real AUV system performance.